Pendidikan Kesehatan Untuk Meningkatkan Pengetahuan Mengenai Tanda Bahaya Nifas di Klinik Anisa Tahun 2024 - Indriani, Putu Lusita Nati; Sari, Rini Gustina; Sari, Erma Puspita (Yayasan Daarul Huda Kruengmane, 2024)
The maternal mortality rate related to pregnancy, childbirth and postpartum is 359 per 100,000 live births, according to the Indonesian Demographic and Health Survey (SDKI). Mothers in the postpartum period have a high risk of death; Approximately 60% of maternal deaths occur after delivery, and nearly 50% of postpartum deaths occur within the first 24 hours after delivery. The causes of maternal death during the postpartum period include postpartum complications such as postpartum hemorrhage and postpartum infections. The cause of not knowing the dangers of the postpartum period is the lack of knowledge of postpartum mothers, so that postpartum mothers are not aware if they experience danger signs during the postpartum period. The aim of this community service is to increase the knowledge of postpartum mothers about the danger signs of the postpartum period at the Anisa Clinic, Mainan Village, by providing health education about. The results of this community service activity show that knowledge about the danger signs of the postpartum period has increased.